2012
DOI: 10.1111/j.1745-7599.2012.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy: The sixth vital sign

Abstract: The NVS takes about three minutes to administer and the assessment is easily accomplished during the initial visit for each patient. Healthcare providers will then be aware of the health literacy level of each patient and base their communication appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 13 publications
3
56
0
5
Order By: Relevance
“…This finding is consistent with the study results of Heinrich (2012) that found no significant correlation between age and health literacy. However, a significant correlation was found between income and health literacy in this population which is supported by the findings of Heide and colleagues (2013).…”
Section: Total Number Of Participants (N) = 19supporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with the study results of Heinrich (2012) that found no significant correlation between age and health literacy. However, a significant correlation was found between income and health literacy in this population which is supported by the findings of Heide and colleagues (2013).…”
Section: Total Number Of Participants (N) = 19supporting
confidence: 93%
“…Furthermore, as expected, this study also found a strong correlation between education and health literacy in this population (Nielson-Bohlman, et al, 2004;& Heinrich, 2012). Chen et al (2014) also reported the significant correlation between health literacy and knowledge.…”
Section: Total Number Of Participants (N) = 19supporting
confidence: 84%
“…[11,33] Consequently, providers may want to spend additional time discussing analgesic medications with their MA patients in order to correct misinformation and answer questions, particularly as MA patients are at risk for having lower levels of health literacy relative to the general population. [34] The current study also found similar rates of analgesic prescription use between MAs and NHBs. The majority of the racial/ethnic disparities literature has failed to report differential rates of treatment between Hispanics and NHBs -focusing solely on each minority groups' comparison with NHWs.…”
Section: Discussionsupporting
confidence: 61%
“…Caregiver preparedness is thus conceptually related to perceived control by findings that prepared individuals tend to have more knowledge, higher self-efficacy (Miller et al, 2013), higher incomes (Paulson & Bassett, 2015) and typically greater access to resources (Heinrich, 2012).…”
Section: Perceived Control -Caregiver Preparednessmentioning
confidence: 99%